Optimization Of The Use Of Promotional Tools To Improve Students' Abilities In Solving Measurement Problems - Baidullah; Asdarina, Orin; Khatimah, Husnul (STMIK Indonesia Banda Aceh, 2025)
Mathematics lessons are often considered as frightening learning material for most students. In the view of students, mathematics is considered a complex subject because it involves various confusing formulas and concepts. The existing facts that occurred in the even semester of the 2022/2023 academic year, based on the results of the initial test given to grade IV students of SDN 4 Jeumpa on the Geometry and Measurement learning material were still very low, namely out of 18 students, only 1 (5.5%) student got a score of 80 or had reached the KKM, while 94.4% of students' level of mastery of the material given was still low. This study uses a qualitative descriptive research approach. Data collection techniques in this study are tests and observations. The tests conducted were pretest and posttest. The questions given in the pretest and posttest were 5 descriptive questions. The data analysis technique used is descriptive data analysis, namely data obtained from the pretest and posttest. From the research results that have been obtained, it can be concluded that there has been an increase in students' ability to solve measurement problems with the help of the use of teaching aids, namely an increase of 72.3% of students who have been able to solve the problems given related to measurement material.